Paternalism in family firms’ successor selection - Jorge, Sílvia Ferreira (2020)
The objective of this paper is to provide insight on the impact that emotional factors have on successor selection in family firms highlighting the role played by the founder’s paternalistic leadership style on family firm successor selection. In order to do so, we model games for different paternalistic leadership styles of the founder towards successor selection and then analytically compare the results. Our paper contributes to the analysis of the impact of the type of paternalistic leadership type has, including the role emotional factors play on the challenging moment of family firm succession. The Nash equilibrium results show that the founder’s paternalistic leadership style plays a key role to ensure firm continuity as well as secure that the founder’s preferred successor is indeed appointed successor. Additionally, our findings emphasize that the emotional factors are crucial in determining the successor outcome.